About : Apex Journal of Business and Management Vol.2 - Prasai, Kul Prasad (Apex Journal of Business and Management, 2024)
The journal uses a rigorous peer-review process, led by a team of experts from Nepal and abroad, to ensure high quality and impact of published research and writing in pursuit of productive and practicable innovation. Articles are subject to initial editor screening followed by a blind peer review before publication. Submissions are invariably checked for plagiarism. Manuscripts must be between5 to 20 pages, in APA formats, that is between (3000 to 8000 words), excluding references. AJBM calls scholars, managers, academicians, scientists, industrial professionals and researchers from all over the world to submit their unpublished original work for inclusion in our upcoming issue.All submissions are reviewed and evaluated based on originality, technical research, and relevance to journal contributions. AJBM highly welcomes theoretical, technical, research, as well as empirical papers in the area of business, management, social science, technology innovation and emerging trends. All the accepted articles will be published in the upcoming issue of the journal with Onlineand Print.